What Is Successful Writing? An Investigation Into the Multiple Ways Writers Can Write Successful Essays. (April 2014) - Crossley, Scott A.; Roscoe, Rod; McNamara, Danielle S.
This study identifies multiple profiles of successful essays via a cluster analysis approach using linguistic features reported by a variety of natural language processing tools. The findings from the study indicate that there are four profiles of successful writers for the samples analyzed. These four profiles are linguistically distinct from one another and demonstrate that expert human raters examine a number of different linguistic features in a variety of combinations when assessing writing proficiency and assigning high scores to independent essays (regardless of the scoring rubric considered). The writing styles in the four clusters can be described as action and depiction style, academic style, accessible style, and lexical style . The study provides empirical evidence that successful writing cannot be defined simply through a single set of predefined features, but that, rather, successful writing has multiple profiles. While these profiles may overlap, each profile is distinct.